From terpyridine-based assemblies to metallo-supramolecular polyelectrolytes (MEPEs) - Schwarz, Guntram; Haßlauer, Iris; Kurth, Dirk G. (Advances in colloid and interface science, 2014)
Introducing metal ion coordination as bonding motive into polymer architectures provides new structures and properties for polymeric materials. The metal ions can be part of the backbone or of the side-chains. In the case of linear metallo-polymers the repeat unit bears at least two metal ion receptors in order to facilitate metal-ion induced self-assembly. If the binding constants are sufficiently high, macromolecular assemblies will form in a solution. Likewise, polymeric networks can be formed by metal ion induced crosslinking. The metal ion coordination sites introduce dynamic features, e.g. for self-healing or responsive materials, as well as additional functional properties including spin-crossover, electro-chromism, and reactivity. Terpyridines have attracted attention as receptors in metallo-polymers due to their favorable properties. It is well suited to assemble linear rigid-rod like metallo-polymers in case of rigid ditopic ligands. Terpyridine binds a large number of metal ions and are readily functionalized giving rise to a plethora of available ligands as components in metallo-polymers. By the judicious choice of the metal ions, the design of the ligands, the counter ions and the boundary conditions of self-assembly, the final structure and properties of the resulting metallo-polymers can be tailored at all length scales. Here, we review recent activities in the area of metallo-polymers based on terpyridines as central metal ion receptors. [Display omitted] •We present recent activities in the area of metallo-polymers based on terpyridines.•Terpyridines serve as receptors for metal-ion induced self-assembly of versatile structures.•The modular setting based on ligands, metal ions and counter ions give rise to tailor properties and design of the resulting metallo-polymer.•The assembly structure range from mononuclear complexes (1D) to networks or liquid crystalline structures (3D).•Counter ions are given particular attention facilitating 3D structures with spin-crossover or electrorheological properties